Motivating students to learn - Wentzel, Kathryn R.; Brophy, Jere E. (New York : Routledge, 2014)
Written specifically for teachers, this book offers a wealth of research-based principles for motivating students to learn. Its focus on motivational principles rather than motivation theorists or theories leads naturally into discussion of specific classroom strategies. Throughout the book these principles and strategies are tied to the realities of contemporary schools (e.g., curriculum goals) and classrooms (e.g., student differences, classroom dynamics). The author employs an eclectic approach to motivation that shows how to effectively integrate the use of extrinsic and intrinsic strategies. Guidelines are provided for adapting motivational principles to group and individual differences and for doing'repair work' with students who have become discouraged or disaffected learners. -- Provided by publisher.
Machine generated contents note: 1.Introduction to Student Motivation -- 2.Classroom Goals: What Is It That I Want to Do? -- 3.Extrinsic Goals and Incentives: What Am I Supposed to Do? -- 4.Intrinsic Motivation and Values: Is This Important and Enjoyable to Do? -- 5.Supporting Intrinsic Motivation and Values by Making Learning Attractive -- 6.Socializing Uninterested or Alienated Students -- 7.Beliefs about Ability, Causality, and Control: Can I Do It? What Causes Success and Failure? -- 8.Rebuilding Discouraged Students' Confidence and Willingness to Learn -- 9.Relationships and Classroom Community: Does Anybody Care? -- 10.Stimulating Students' Motivation to Learn -- 11.Adapting to Differences in Students' Motivational Patterns -- 12.Looking Back and Ahead: Integrating Motivational Goals into Your Planning and Teaching.
Includes bibliographical references and index.
Keywords: Motivation in education